Editorial Introduction - Miguel, Paulo Augusto Cauchick (Brazilian Journal of Operations & Production Management, 2010)
On behalf of the Editorial Board, we are happy to deliver the first issue of volume 5 (2008) of the Brazilian Journal of Operations & Production Management. We appreciate all the academicians who support and contribute to the editorship. The accomplishment of this issue would not be possible without the work of our editorial review board. We would like to take this opportunity to acknowledge their contribution to the journal referral process. In this issue we have the pleasure of announcing that Barbara Flynn of Indiana University and Robert Young of North Carolina State University, both from the USA, are now part of the editorial advisory board. Sérgio Gouvêa da Costa and I have formally invited them and we are honoured they kindly accepted. We hope the readers find the articles in this issue a useful source within the scope ofproduction engineering and operations management.